Stock structure of Lethrinus laticaudis (Lethrinidae) across northern Australia determined using genetics, otolith microchemistry and parasite assemblage composition - Barton, D.; Taillebois, L.; Taylor, J.; Crook, D.; Saunders, T.; Hearnden, M.; Greig, A.; Welch, D.; Newman, Stephen; Travers, M.; Saunders, R.; Errity, C.; et al. (CSIRO Publishing, 2018)
The grass emperor Lethrinus laticaudis is a conspicuous element of the commercial and recreational catch from nearshore reef systems across northern Australia. The nearshore reef systems across northern Australia are exposed to increasing levels of fishing pressure from commercial and recreational fishers. To inform ongoing management of this species, the present study examined the stock structure of L. laticaudis across northern Australia using a combination of complementary techniques. In all, 342 L. laticaudis samples were collected from 13 locations in the coastal waters of northern Australia ranging from the Pilbara region of Western Australia to Moreton Bay in south-east Queensland. Population genetic analyses using microsatellite markers demonstrated that there were at least four genetically distinct populations across northern Australia with gene flow between management jurisdictions (with significantly more separation between Western Australian and Northern Territory locations than between Northern Territory and Queensland locations). An isolation by distance effect was evident (genetic differences increasing linearly with distance). Otolith microchemistry and parasitology analyses indicated some spatial structuring of populations within broader regions. These findings of restricted connectivity at small spatial scales suggest that L. laticaudis is vulnerable to localised depletion in areas where fishing effort is concentrated. This conclusion is consistent with recent observations of fishery declines in heavily fished locations.